Synthesis and Photoluminescence Properties of a Red‐Emitting Phosphor Sr9Mg1.5(PO4)7:Eu3+. Issue 3 (15th March 2016) - Sun , Wenzhi; Jia , Yonglei; Ma, Tengfei; Li, Da; Li , Haifeng; Jiang, Lihong; Zhang, Su; Fu , Jipeng; Pang, Ran; Li, Chengyu
Abstract: A novel red‐emitting Sr9 Mg1.5 (PO4 )7 :Eu 3+ phosphor was synthesized via high‐temperature solid‐state reaction. The crystal structure was confirmed by Rietveld refinement method. The luminescence properties were investigated by diffuse reflection spectra, photoluminescence excitation spectra and emission spectra as well as temperature‐dependent luminescence spectra. The phosphor shows strong absorption at 395 nm and 466 nm, which matches well with the commercial n‐ultraviolet and blue chips. Upon excitation at 395 nm, the phosphor exhibits bright red emission with the dominate peak at about 617 nm, assigning to 5 D0 – 7 F2 transition of Eu 3+ . Meanwhile, the concentration quenching mechanism, fluorescence lifetime and thermal stability have been investigated in detail. The Commission International de I'Eclairage (CIE) coordinates of Sr9 Mg1.5 (PO4 )7 :0.40Eu 3+ are very close to those of National Television Standard Committee (NSTC) standard red light. The experimental data indicate Sr9 Mg1.5 (PO4 )7 :Eu 3+ phosphor may be promising as a red‐emitting phosphor for white light emitting diodes. Abstract : A novel red‐emitting Sr9 Mg1.5 (PO4 )7 :Eu 3+ phosphor was synthesized via high‐temperature solid‐state reaction. The phosphor can be excited efficiently by n‐UV and blue light, and exhibit bright red emission with the dominate peak at about 617 nm, assigning to 5 D0 – 7 F2 transition of Eu 3+ . The excellent thermal stability of the phosphor demonstrates it may serve as a potential red‐emitting phosphor for white LEDs application.